Exploring the Challenges and Opportunities of Funding in Public Universities in Ghana in the Context of Declining State Subvention - Mensah, Paul Kwasi (Advances in Social Sciences Research Journal, 2024)
The role of tertiary education for socio-economic development globally demands adequate funding to effectively train high-quality experts in the current knowledge economy. However, the funding support from government for tertiary education institutions in Ghana after independence had declined due to national financial crisis and equally important demand for social services and other infrastructure needs. The study objectives aim at examining the funding challenges in public universities and how these universities explore the available opportunities to mobilize extra resources for effective delivery of their core mandate. This study used a mixed method approach for data collection. The findings reveal that there are delays in state subvention payments which force some universities to contract bank loans at high interest rates to pay staff salaries and government does not pay the accrued interest. Further, the state issue policy directives to restrict resource mobilization efforts of the universities. Despite the state funding challenges, the study findings reveal that the universities are not ready for self-financing and would require state funding to deliver effectively. Other funding opportunities that could be accessed to supplement state subvention are public-private-partnership (PPP) commercial ventures, endowment funds and prudent management of available fund. The need to manage effects of state regulatory policies to minimize industrial conflict in the universities is imperative. The universities should utilize their varied expertise to establish a consortium of training of trainers for grant proposal writing and other capacity development programmes for commercial purposes to mobilize funds